Terkulov V. I. About the methodology of anclave dialect research - Terkulov V. I. (Philological Treatises, 2020)
This article is devoted to the definition of the methodological basis of the so called enclave dialectology, which seems to the author to be the section of the traditional dialectology. This section deals with the study of the dialects of the language that functions on the territory where the foreign language is used. This research is the basis for the further analysis of Ukrainian dialects in the Russian Federation that is executed by the group of linguists of Horlivka state pedagogical institute of foreign languages who are led by the author and supported by the funds of fundamental researches of Ukraine and Russia.